Determination of Cr(III) in Industrial Effluents by Zinc Oxide-Tin(IV) Antimonophosphate Nanocomposite Based Ion Selective Electrode - Kaushal, Sandeep; Kaur, Mandeep; Mittal, Susheel Kumar; Singh, Pritpal (Asian Journal of Chemistry, 2017)
This investigation focuses on trace level determination of chromium(III) ions in industrial effluents by a novel zinc oxide-tin(IV) antimono-phosphate nanocomposite based ion selective electrode. The distribution studies confirmed the high selectivity of the nanocomposite material for Cr(III) ions which was thus used as an electroactive material for fabrication of Cr(III) selective electrode. The material was characterized by FTIR, X-ray, SEM, TEM, EDX and TGA techniques. The membrane sensor exhibits a stable sub-Nernstian response to chromium(III) ions over a wide concentration range of 1 × 10-7 to 1 × 10-2 M in the pH range 2.0-8.5. The dynamic response time, limit of detection, life span and slope of the proposed sensor were 12 s, 1.0 × 10-8 M, 4 months and 15 mV/decade, respectively. The proposed sensor was successfully used for estimation of the activity of Cr(III) ions in electroplating and leather tannery effluents. The results obtained were validated by comparison with those obtained by UV-visible spectrophotometric and atomic absorption spectrometric techniques. The analytical utility of the proposed sensor was established by potentiometric titration of Cr(III) ions with EDTA solution.